2006
DOI: 10.1002/jcp.20656
|View full text |Cite
|
Sign up to set email alerts
|

Wnt induction of chondrocyte hypertrophy through the Runx2 transcription factor

Abstract: We investigated the molecular mechanisms underlying canonical Wnt-mediated regulation of chondrocyte hypertrophy using chick upper sternal chondrocytes. Replication competent avian sarcoma (RCAS) viral over-expression of Wnt8c and Wnt9a, upregulated type X collagen (col10a1) and Runx2 mRNA expression thereby inducing chondrocyte hypertrophy. Wnt8c and Wnt9a strongly inhibited mRNA levels of Sox9 and type II collagen (col2a1). Wnt8c further enhanced canonical bone morphogenetic proteins (BMP-2)-induced expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(180 citation statements)
references
References 55 publications
6
166
1
7
Order By: Relevance
“…In addition, Qiao et al (2004) reported that IGF-1 stimulates the activity of the transcription factor RUNX2, through a PI3K-dependent but Akt-independent signaling pathway. Both Fra-1 and Runx2 are known downstream targets of the Wnt or cat/TCF signaling pathway (Mann et al, 1999;Dong et al, 2006). In this study, we found that insulin stimulates PAK-1 phosphorylation/activation in multiple cancer cell lines and in mouse intestinal tissues on Thr423, a target residue of phosphoinositide-dependent kinase isozyme-1, hence bypassing Akt (King et al, 2000).…”
Section: Discussionmentioning
confidence: 63%
“…In addition, Qiao et al (2004) reported that IGF-1 stimulates the activity of the transcription factor RUNX2, through a PI3K-dependent but Akt-independent signaling pathway. Both Fra-1 and Runx2 are known downstream targets of the Wnt or cat/TCF signaling pathway (Mann et al, 1999;Dong et al, 2006). In this study, we found that insulin stimulates PAK-1 phosphorylation/activation in multiple cancer cell lines and in mouse intestinal tissues on Thr423, a target residue of phosphoinositide-dependent kinase isozyme-1, hence bypassing Akt (King et al, 2000).…”
Section: Discussionmentioning
confidence: 63%
“…(35,53) This mimics in some way the natural process of chondrocyte hypertrophy and osteogenesis. Seven days after application of BIO, the expression of SOX9 was decreased, and the expression of RUNX2 was prominently detected [although it was not expressed initially in the chondrocytes (day 3)] and compared with the DMSO control.…”
Section: Sox9 Enhances the Degradation Of Runx2 Through The Lysosomalmentioning
confidence: 96%
“…(1,10,31) Indeed, it has been found that SOX9 exerts a dominant function over RUNX2 in mesenchymal precursors. (32) RUNX2 regulates chondrocyte maturation and also chondrocyte hypertrophy, (33)(34)(35) which suggests that RUNX2 suppresses SOX9 at some stage during skeletal development. Here we determined the nature of RUNX2-SOX9 interactions and the mechanism by which SOX9 regulates RUNX2 function.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with TMP and stabilization of DD-ICAT resulted in downregulation of the β-catenin/TCF target genes Axin2, Enc1, Mecom, and Runx2 (Fig. 3D) (23,24,27,28), as well as down-regulation of a luciferase reporter driven by a 7× repeat of the canonical TCF binding sequence (Fig. 3E) (29).…”
Section: Myc-induced Lymphomas Exhibit Addiction To Mutant β-Cateninmentioning
confidence: 99%